2017
DOI: 10.1158/0008-5472.can-16-1621
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Bacteria against Solid Tumors

Abstract: Intentional bacterial infections can produce efficacious antitumor responses in mice, rats, dogs, and humans. However, low overall success rates and intense side effects prevent such approaches from being employed clinically. In this work, we titered bacteria and/or the proinflammatory cytokine TNFα in a set of established murine models of cancer. To interpret the experiments conducted, we considered and calibrated a tumor-effector cell recruitment model under the influence of functional tumor-associated vascu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Different mathematical models have been proposed to simulate tumor-immune system interactions 21,22,[49][50][51][52][53][54][55][56][57][58][59] and the synergistic effects of radiotherapy with the immune system and immunotherapy. 22,[60][61][62][63] To demonstrate immunologic consequences of sequencing radiotherapy and surgery, we extended the established Kuznetsov model and its parameterization as previously discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Different mathematical models have been proposed to simulate tumor-immune system interactions 21,22,[49][50][51][52][53][54][55][56][57][58][59] and the synergistic effects of radiotherapy with the immune system and immunotherapy. 22,[60][61][62][63] To demonstrate immunologic consequences of sequencing radiotherapy and surgery, we extended the established Kuznetsov model and its parameterization as previously discussed.…”
Section: Discussionmentioning
confidence: 99%
“…When Salmonella was administrated into the solid tumor within hemorrhagic area, the bacteria will proliferate and consume the oxygen and nutrients, leading to necrotic regions of hemorrhaging area, destroy the blood vessels, and finally reduce the proliferation of tumor cells [34,124]. Most bacteria have the ability to attack and colonize cancer cells, and in best cases, this leads to the treatment of cancer completely [132][133][134].…”
Section: Oncolytic Bacteriamentioning
confidence: 99%
“…When Salmonella was administrated into the solid tumor within hemorrhagic area, the bacteria will proliferate and consume the oxygen and nutrients, leading to necrotic regions of hemorrhaging area, destroy the blood vessels, and finally reduce the proliferation of tumor cells [ 34 , 124 ]. Most bacteria have the ability to attack and colonize cancer cells, and in best cases, this leads to the treatment of cancer completely [ 132 134 ]. The recent studies demonstrated that the microbiome within the human body targeted the tumor cells because of decreased immune activity in the necrotic cores of tumor [ 135 ]; some bacteria can grow into tumors that are preferred for reproduction by consuming food and oxygen, causing cancer cells to starve and suffocate.…”
Section: Bacteria In Cancer Therapymentioning
confidence: 99%
“…The dynamics of targeted cancer therapy have been investigated using a mathematical model of somatic evolution (19). Bacteria and/or pro-inflammatory cytokine TNF in a set of established murine modes of cancer was presented in (20). An agent-based method of immune and epithelial cell interactions in breast lobular epithelium was developed to earn perspicacity towards the prognostic potential of inflammation (21).…”
Section: Introductionmentioning
confidence: 99%